2019
DOI: 10.2147/ijn.s199624
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effect of surface treatment on the brain delivery of curcumin nanosuspension: in vitro and in vivo studies</p>

Abstract: Background: Curcumin, a bioactive component with multiple characteristics, has been shown to have many therapeutic effects. However, there are several limitations regarding the use of curcumin such as instability, low solubility, poor bioavailability, and rapid elimination. Different approaches have been used to solve these problems. Materials and methods: In this study, surface-modified nanosuspension (NS) is investigated as a novel brain delivery system. Two different metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 59 publications
(79 reference statements)
2
13
0
Order By: Relevance
“…Curcumin nanosuspensions, consisting of stable nanoscale droplets of the compound with surfactants and biopolymers, improved solubilization and increased intravenous plasma distribution to vital organs compared with standard curcumin. Higher levels of curcumin in male Wistar rat brains were discovered when delivered via Tween 80-coated nanoparticles (NPs) in comparison to curcumin solution [37]. The mechanism of action exerted by curcumin in neuroblastoma cells involved the regulation of PTEN-Akt (phosphatase and tensin homolog-protein kinase B), NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), and p53 (tumor protein P53), signaling, activation of the apoptosis cascade, and mitochondrial dysfunction [36].…”
Section: Nano-phytopharmaceuticals In Neurological (Cns) Disordersmentioning
confidence: 99%
“…Curcumin nanosuspensions, consisting of stable nanoscale droplets of the compound with surfactants and biopolymers, improved solubilization and increased intravenous plasma distribution to vital organs compared with standard curcumin. Higher levels of curcumin in male Wistar rat brains were discovered when delivered via Tween 80-coated nanoparticles (NPs) in comparison to curcumin solution [37]. The mechanism of action exerted by curcumin in neuroblastoma cells involved the regulation of PTEN-Akt (phosphatase and tensin homolog-protein kinase B), NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), and p53 (tumor protein P53), signaling, activation of the apoptosis cascade, and mitochondrial dysfunction [36].…”
Section: Nano-phytopharmaceuticals In Neurological (Cns) Disordersmentioning
confidence: 99%
“…TPGS-NS and Tween-NS exhibit rapid and complete dissolution in phosphate-buffered saline, compared to the slower and incomplete dissolution of pure curcumin. Moreover, the IV administration of these nanosuspensions increases curcumin concentrations in the plasma, brain, heart, and digestive system in comparison to standard curcumin at 10 mg/kg [ 112 ].…”
Section: Potential Solutions For the Use Of Curcumin In The Nervoumentioning
confidence: 99%
“…For example, Paclitaxel nanosuspension with TPGS significantly prevented the drug resistant of P-gp for H460 human cancer cells and was observed five times higher tumor inhibition than the paclitaxel solution (Gao et al., 2014). Tween 80 as the nanosuspension stabilizer could contribute to the transportation of curcumin to brain in the way of receptor-mediated endocytosis (Dibaei et al., 2019). In a recent study, the charges of stabilizers were proven the effect on the mucoadhesiveness and permeation of cell monolayers, which confirmed that positively charged nanosized clarithromycin was observed better mucoadhesiveness than the not charged and the negatively charged nanocrystals, and both charged nanocrystals reflected an improved drug delivery compared to the uncharged (Soisuwan et al., 2019).…”
Section: Tailor-made Drug Delivery Based On Nanocrystalsmentioning
confidence: 99%